2013
DOI: 10.1111/1574-6941.12053
|View full text |Cite
|
Sign up to set email alerts
|

Impact of water quality on the bacterial populations and off-flavours in recirculating aquaculture systems

Abstract: A variety of factors affecting water quality in recirculating aquaculture systems (RAS) are associated with the occurrence of off-flavours. In this study, we report the impact of water quality on the bacterial diversity and the occurrence of the geosmin-synthesis gene (geoA) in two RAS units operated for 252 days. Unit 2 displayed a higher level of turbidity and phosphate, which affected the fresh water quality compared with unit 1. In the biofilter, nitrification is one of the major processes by which high wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 54 publications
1
52
0
2
Order By: Relevance
“…In our previous study, we reported that the detected Streptomyces, Myxococcales, Sorangium and Nannocystis coincided with the detection of geosmin in trout raised in RAS (Auffret et al 2011(Auffret et al , 2013, and there was a positive correlation between Nannocystis in the fish tank and the detection of geosmin in fish tissue. Auffret et al (2013) also speculated that P could be associated with the abundance of Sorangium and the geosmin-synthesis gene that could enhance the geosmin production in RAS.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In our previous study, we reported that the detected Streptomyces, Myxococcales, Sorangium and Nannocystis coincided with the detection of geosmin in trout raised in RAS (Auffret et al 2011(Auffret et al , 2013, and there was a positive correlation between Nannocystis in the fish tank and the detection of geosmin in fish tissue. Auffret et al (2013) also speculated that P could be associated with the abundance of Sorangium and the geosmin-synthesis gene that could enhance the geosmin production in RAS.…”
Section: Discussionmentioning
confidence: 74%
“…Transition metal concentrations were determined using an an ion exchange chromatography technique (ICS-3000, Dionex). The same analyses were performed according to the method described by Auffret et al (2013) and furnished in the Appendix.…”
Section: Water Analysismentioning
confidence: 99%
“…TOCs are produced by several species of cyanobacteria (also known as blue-green algae) and by non-photosynthetic Streptomyces bacteria (Gram-positive, filamentous bacteria), but recent research indicates that other bacteria, e.g. species within the order Myxococcales, may also produce off-flavours in some aquaculture systems (Zaitlin & Watson 2006, Auffret et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Ion Torrent PGM has been used for community analyses of uranium mine tailings that had particularly high pH and low permeability 6 , of recirculating aquaculture systems 7 , of hydrocarbon-contaminated Arctic soils , of the human and animal bodies [13][14][15][16] and of anaerobic digesters 17 .…”
Section: Introductionmentioning
confidence: 99%